ANTIDIABETIC AND TOXICITY ASSESSMENT OF COMBINATION OF PIPER NIGRUM AND ARTOCARPUS HETROPYLLUS - Urmila Rathore; Shweta Panwar; Dr Tanu Bhargava, Dr Narendra Mandoria (Journal of Medical Care Research and Review, 2023)
The worldwide prevalence of DM has risen dramatically over the past two decades, from an estimated 30 million cases in 1985 to 285 million in 2010. Based on current trends, the International Diabetes Federation projects that 438 million individuals will have diabetes by the year 2030. However, on chronic usage most of these agents produced several side effects, including hypoglycemic coma, insulin resistance, hyper-sensitivity, cholesterol, jaundice, abdominal pain, anorexia and metallic taste [4]. For various reasons in recent years, the popularity of herbal medicines in diabetic control has increased. Natural plant drugs are frequently considered to be less toxic with lower side effects than synthetic ones [7].Therefore searching herbal product with anti-diabetic activity possessing fewer side effects receives considerable publicity and provides an opportunity to cure this disease. Keywords: Antidiabetic, Prevalence, Hyperglycaemia, Toxicity, Diabetic Anatomy etc.